Study on the Implementation of Physical Education Evaluation at SMP Negeri 1 Batang Anai - Maison, Maison; Fazly, Marzahren; Fitria, Ilmi (Yayasan Sekora, 2018)
Based on observations made by the author in the field, physical education teachers have not been effective in evaluating learning in Sports and Health Physical Education (PJOK), so that the assessment of students is not based on the abilities of the students. The purpose of this study was to determine the planning of implementation and evaluation results of PJOK learning. The research question posed was how to plan, implement and evaluate the learning outcomes of PJOK subjects at SMP Negeri 1 Batang Anai. This type of research is classified as a descriptive study. The population in this study were students of class VIII SMP Negeri 1 Batang Anai, totaling 412 people. Samples were taken using proportional random sampling technique (10% of the total population), thus the number of samples was 41 people. The type of data in this research is primary data, data that is directly obtained from respondents by distributing questionnaires to students. Furthermore, the data were analyzed using percentage techniques using the ideal value score. Based on the results of data analysis, it shows that the evaluation planning variable has an achievement level of 78.36%, is in a good classification, the evaluation implementation variable has an achievement level of 74.88%, is in a good classification and the evaluation result variable has an achievement level of 62.63. % classification 61% - 80% are in good classification. Thus it means that physical education teachers carry out the planning and implementation of evaluations and provide good evaluation results.